A semi-aromatic polyamide composition and its preparation method and application

By optimizing the end amine and end carboxyl concentrations of semi-aromatic polyamide resins, and combining glass fibers and elastomers, a semi-aromatic polyamide composition with excellent hydrolysis resistance was prepared, which solved the hydrolysis of existing materials in high temperature and high humidity environments. The problem of poor performance meets the requirements of improving durability and application life of automotive cooling systems.

CN117186636BActive Publication Date: 2024-12-31ZHUHAI WANTONG SPECIAL ENG PLASTICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311089110.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2024-12-31
Estimated Expiration
2043-08-28

AI Technical Summary

Technical Problem

The existing semi-aromatic polyamide materials have poor hydrolysis performance in high temperature and high humidity environments, resulting in insufficient durability and application life when used in automotive cooling systems. Especially when the temperature rises after the popularization of engine turbocharger technology, it is difficult to Meet customers' requirements for improving coolant resistance performance.

Method used

By optimizing the end amine and end carboxylic concentrations of the semiaromatic polyamide resin and combining an appropriate amount of glass fiber and elastomer, a semiaromatic polyamide composition is prepared, including 52-75 parts of semiaromatic polyamide resin, 25- 45 parts of glass fiber and 0-3 parts of elastomer are used to extrude granulation process by twin screw extruder to control the relative viscosity of the material and the diameter of the glass fiber to improve the material's hydrolysis resistance.

Benefits of technology

The tensile strength retention rate after aging of the coolant at 135℃/1000h is achieved, which significantly improves the hydrolysis resistance of semi-aromatic polyamide materials and is suitable for automotive cooling system components in high temperature and high humidity environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A semi-aromatic polyamide composition comprises the following components by weight: 52-75 parts of a semi-aromatic polyamide resin; 25-45 parts of a glass fiber; and 0-3 parts of an elastomer; wherein the semi-aromatic polyamide resin has a terminal amine concentration of 100-150 mol / t, a terminal carboxyl concentration of ≤50 mol / t, and an average diameter of the glass fiber of 0.1-15 microns. The present invention can significantly improve the hydrolysis resistance by investigating the terminal amine group, terminal carboxyl concentration, and relative viscosity of the semi-aromatic polyamide and exploring the diameter of the glass fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a semi-aromatic polyamide composition and a preparation method and application thereof. Background Art

[0002] Semi-aromatic polyamide resin has excellent mechanical strength, heat resistance, chemical resistance, wear resistance and self-lubrication, and has a low friction coefficient. It is widely used in electronic and electrical, automotive parts, furniture, building materials and fiber fields, and has become one of the most important engineering plastics. Due to the presence of amide bonds, polyamide materials will hydrolyze in high temperature and high humidity environments, resulting in reduced product performance and shortened service life. The automotive cooling system is an important part of the engine system. At present, automotive engines generally use water-cooled cooling systems. The coolant (generally a 1:1 mixture of ethylene glycol and water, and may also contain various additives such as corrosion inhibitors, defoamers and stabilizers) is driven by a water pump for forced circulation. The components through which the coolant flows include the water pump, engine cooling water jacket, radiator, thermostat, water outlet and system connection pipes of the cooling system, etc., which takes away the excess heat of the engine and then dissipates it to the surrounding environment through the radiator. Most water pump materials are made of polyamide, but with the maturity and extensive application of engine turbocharging technology, the temperature in the engine compartment is getting higher and higher, which is more serious for water pump impellers and water pump housings that are eroded by coolant, as well as other parts with high strength and size requirements. At the same time, some OEMs currently require that the tensile strength of polyamide compositions after aging with 135℃ / 1000h coolant should be ≥105MPa, so there are certain requirements for the initial tensile strength of semi-aromatic polyamide compositions.

[0003] As the size of engines becomes smaller, the requirements for coolant resistance will become higher and higher. Therefore, for engine cooling system applications, long-term hydrolysis / alcoholysis resistant materials must be developed to meet customers' increasingly high requirements. Existing technologies mainly achieve the improvement of hydrolysis resistance through the following methods:

[0004] CN108587151A discloses an alcoholysis-resistant nylon material used in automobile cooling systems and a preparation method thereof, which includes the following raw materials by weight percentage: 47-90% nylon; 10-50% alcoholysis-resistant glass fiber; 0.5-2% alcoholysis-resistant additive; 0-1% lubricant and antioxidant. The technical scheme of the invention is to increase the interface bonding force between nylon and glass fiber by reacting multiple active functional groups carried by the copolymer of ethylene and maleic anhydride with the active functional groups on the surface of glass fiber and the terminal functional groups of the nylon molecular chain respectively, which will effectively improve the alcoholysis resistance of the composite material.

[0005] CN113773640A discloses a hydrolysis-resistant glass fiber reinforced polyamide composite material, which is prepared from the following components by weight: 30-80 parts of polyamide resin, 0.5-1.0 parts of dispersant, 3-10 parts of toughening agent, 0.05-0.2 parts of initiator, 0.1-0.2 parts of nucleating agent, 10-50 parts of modified glass fiber, and 0.2-0.4 parts of antioxidant; wherein the modified glass fiber is a glass fiber coated with glycidyl methacylate (GMA) on the outer surface. The technical solution of the invention uses glass fiber modified with GMA, which is more conducive to improving the mechanical properties of the polyamide composite material and the mechanical property retention rate after high-temperature boiling. At the same time, the addition of GMA can effectively avoid the degradation tendency caused by the hydrolysis of the amide bond in the polyamide molecular chain, and ensure the melt strength and mechanical properties.

[0006] It can be seen that the main technical solution of the prior art is to improve the hydrolysis resistance of the polyamide composition by increasing the bonding force between the glass fiber and the polyamide resin. It has a certain improvement effect in aliphatic polyamides with poor hydrolysis resistance such as PA6 and PA66 materials, but the improvement effect is not obvious in semi-aromatic polyamide systems with relatively good water resistance. Summary of the invention

[0007] The object of the present invention is to provide a semi-aromatic polyamide composition with good hydrolysis resistance and a tensile strength of ≥105MPa after aging with a coolant at 135°C / 1000h.

[0008] The present invention is achieved through the following technical solutions:

[0009] A semi-aromatic polyamide composition, comprising the following components in parts by weight:

[0010] 52-75 parts of semi-aromatic polyamide resin;

[0011] Glass fiber 25-45 parts;

[0012] Elastomer 0-3 parts;

[0013] Wherein, the terminal amine concentration of the semi-aromatic polyamide resin is 100-150 mol / t, and the terminal carboxyl concentration is ≤50 mol / t;

[0014] The average diameter of the glass fiber is 0.1-15 microns;

[0015] The semi-aromatic polyamide resin is selected from at least one of PA6T / 6I, PA6T / 6I / 66, PA6T / M5T, PA5T / 6T, PA9T, PA9T / 66, PA10T, PA10T / 66, PA10T / 10I, PA10T / 1010, PA10T / 1012, and PA12T.

[0016] Preferably, the semi-aromatic polyamide resin has a terminal amine group concentration of 110-130 mol / t and a terminal carboxyl group concentration of 30-40 mol / t.

[0017] The test method for the terminal amine concentration in the semi-aromatic polyamide composite resin matrix is ​​as follows: the terminal amine content of the sample is titrated with a fully automatic point titrator, the semi-aromatic polyamide resin content is 0.5g, 45ml of phenol and 3ml of anhydrous methanol are added, heated to reflux to dissolve, insoluble matter is filtered out, and the terminal amine content is titrated with a calibrated concentration of hydrochloric acid standard solution. The test method for the terminal carboxyl concentration in the semi-aromatic polyamide composite resin matrix is ​​as follows: the terminal carboxyl content of the sample is titrated with a fully automatic point titrator, the semi-aromatic polyamide resin content is 0.5g, 50ml of o-cresol is added, heated to reflux to dissolve, insoluble matter is filtered out, and 400μL of formaldehyde solution is quickly added after cooling to room temperature, and the terminal carboxyl content is titrated with a calibrated concentration of potassium hydroxide ethanol standard solution.

[0018] In the present invention, the semi-aromatic polyamide resin is preferably selected from at least one of PA6T / 6I and PA6T / 6I / 66. The preferred semi-aromatic polyamide resin has a higher initial tensile strength.

[0019] The present invention has no limitation on the relative viscosity of the semi-aromatic polyamide. Generally, the relative viscosity of the commercially available semi-aromatic polyamide is 2.2-2.6, preferably 2.4-2.6. The test method is to measure the relative viscosity of the polyamide with a concentration of 0.25 g / dL in 98% concentrated sulfuric acid at 25±0.01°C with reference to GB / T 12006.1 polyamide viscosity determination method.

[0020] The semi-aromatic polyamide of the present invention can be a commercially available product or can be obtained by self-production. The self-production method is as follows: adding diamine and diacid in a pressure autoclave in proportion; then adding a capping agent, a catalyst and deionized water; vacuuming and filling with high-purity nitrogen as a protective gas, heating to 210-230°C within 1-3 hours under stirring, stirring the reaction mixture for 0.5-1.5 hours, and then raising the temperature of the reactants to 230-250°C under stirring; the reaction is continued at a constant temperature and pressure for 1-3 hours, the pressure is kept constant by removing the formed water, the material is discharged after the reaction is completed, and the prepolymer is vacuum dried at 75-85°C to obtain a prepolymer product, and the prepolymer product is solid-phase thickened for 8-12 hours under vacuum conditions of 240-260°C and 40-60 Pa to obtain a polyamide resin.

[0021] The concentration of terminal amine groups and terminal carboxyl groups can be controlled by conventional means such as adjusting the content of the end-capping agent. The end-capping agent can be an amine compound, such as monohydrated ammonia, ethylamine, n-propylamine, n-butylamine, n-pentylamine, n-hexylamine or benzylamine.

[0022] Preferably, the diameter of the glass fiber is 0.1-8 microns.

[0023] The elastomer is selected from at least one of polyethylene elastomer, polypropylene elastomer, EPDM rubber and ethylene-octene copolymer.

[0024] It is possible to choose whether to add 0-2 parts of auxiliary agents according to actual needs; the auxiliary agent is selected from at least one of an antioxidant and a lubricant. The lubricant can be sodium montanate, calcium montanate, lithium stearate, calcium stearate, a small molecule amide compound, a polyol, a polyamine, a hyperbranched polymer or a dendritic polymer, etc.

[0025] The semi-aromatic polyamide composition of the present invention has a tensile strength retention rate of ≥50%, preferably ≥55%, after 135°C / 1000h coolant aging. The testing method is: an ISO standard tensile specimen is placed in a high-pressure tank containing coolant (ethylene glycol and water mixed in a mass ratio of 1:1) (the specimen is completely immersed in the coolant), and then the high-pressure tank is sealed and placed in an aging oven at 135°C for a 1000h high-temperature test.

[0026] The preparation method of the semi-aromatic polyamide composition is characterized by comprising the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder at a temperature range of 270-330° C. and a rotation speed range of 200-500 rpm to obtain the semi-aromatic polyamide composition.

[0027] The semi-aromatic polyamide composition of the present invention is used for preparing hydrolysis-resistant parts, such as water pumps, water valves, thermostats, engine cooling water jackets, water pipe joints, radiators and the like.

[0028] The present invention has the following beneficial effects

[0029] The present invention can significantly improve the hydrolysis resistance by investigating the concentration of terminal amine groups and terminal carboxyl groups of the semi-aromatic polyamide to achieve acid-base balance of the semi-aromatic polyamide composition, and exploring the diameter of the glass fiber and the relative viscosity of the semi-aromatic polyamide. Implementation

[0030] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0031] The sources of raw materials used in the present invention are as follows:

[0032] PA6T6I-A: terminal amine concentration 103 mol / t, terminal carboxyl concentration 46 mol / t, relative viscosity 2.42, homemade;

[0033] PA6T6I-B: terminal amine concentration 148 mol / t, terminal carboxyl concentration 21 mol / t, relative viscosity 2.40, homemade;

[0034] PA6T6I-C: terminal amine concentration 111 mol / t, terminal carboxyl concentration 37 mol / t, relative viscosity 2.46, homemade;

[0035] PA6T6I-D: terminal amine concentration 130 mol / t, terminal carboxyl concentration 32 mol / t, relative viscosity 2.43, homemade;

[0036] PA6T6I-E: terminal amine concentration 128 mol / t, terminal carboxyl concentration 31 mol / t, relative viscosity 2.56, homemade;

[0037] PA6T6I-F: terminal amine concentration 129 mol / t, terminal carboxyl concentration 30 mol / t, relative viscosity 2.20, homemade;

[0038] PA6T6I-G: terminal amine concentration 86 mol / t, terminal carboxyl concentration 43 mol / t, relative viscosity 2.51, homemade;

[0039] PA6T6I-H: terminal amine concentration 102 mol / t, terminal carboxyl concentration 83 mol / t, relative viscosity 2.59, homemade;

[0040] PA6T6I-I: terminal amine concentration 157 mol / t, terminal carboxyl concentration 55 mol / t, relative viscosity 2.44, homemade;

[0041] PA6T6I-J: terminal amine concentration 107 mol / t, terminal carboxyl concentration 124 mol / t, relative viscosity 2.44, homemade

[0042] PA6T / 6I / 66-1: terminal amine concentration 126 mol / t, terminal carboxyl concentration 36 mol / t, relative viscosity 2.43, homemade;

[0043] PA10T: terminal amine concentration 108 mol / t, terminal carboxyl concentration 43 mol / t, relative viscosity 2.53, homemade;

[0044] PA6T / 6I / 66-2: terminal amine concentration 126 mol / t, terminal carboxyl concentration 107 mol / t, relative viscosity 2.43, homemade;

[0045] PA6T / 6I / 66-3: terminal amine concentration 82 mol / t, terminal carboxyl concentration 93 mol / t, relative viscosity 2.51, homemade;

[0046] PA66: terminal amine concentration 113 mol / t, terminal carboxyl concentration 36 mol / t, relative viscosity 2.58, homemade;

[0047] PA66 / 6T: terminal amine concentration 115 mol / t, terminal carboxyl concentration 39 mol / t, relative viscosity 2.43, homemade;

[0048] Glass fiber A: average diameter of 7 μm, purchased from Jushi Group;

[0049] Glass fiber B: average diameter 10 μm, purchased from Jushi Group;

[0050] Glass fiber C: average diameter 11 μm, purchased from Jushi Group;

[0051] Glass fiber D: average diameter 13 μm, purchased from Jushi Group;

[0052] The glass fiber is E-type glass fiber.

[0053] Ethylene-octene copolymer: FUSABOND N216, purchased from Dow Chemical.

[0054] EPDM rubber: FUSABOND N416, purchased from Dow Chemical.

[0055] Embodiment and comparative example The preparation method of the semi-aromatic polyamide composition: according to the ratio, the components are mixed uniformly, and granulated by extrusion through a twin-screw extruder, the temperature of each zone of the screw is set to 110℃-300℃-330℃-320℃-300℃-290℃-280℃-270℃-270℃-280℃-300℃-330℃, and the speed range is 300 rpm to obtain a semi-aromatic polyamide composition.

[0056] Various test methods:

[0057] (1) Tensile strength: The obtained semi-aromatic polyamide resin composition was dehumidified and dried at 120°C for 5 h, the barrel temperature of the injection molding machine was set at 290-330°C for heating and melting, and injection molded into standard tensile specimens. The tensile properties were tested in accordance with the international standard ISO 527-2-2019. The test conditions were: temperature 23°C, tensile rate 10 mm / min.

[0058] (2) Tensile strength retention after hydrolysis resistance test:

[0059] According to ISO standards, two specimens were injected and tested as follows:

[0060] Hydrolysis resistance test 1: Place the ISO standard tensile specimen in a high-pressure tank containing distilled water (the specimen is completely immersed in the coolant), then seal the high-pressure tank and place it in an aging oven at 100°C for a high-temperature test for 168 hours.

[0061] Hydrolysis resistance test 2: Place the ISO standard tensile specimen in a high-pressure tank containing coolant (ethylene glycol and water mixed in a mass ratio of 1:1) (the specimen is completely immersed in the coolant), then seal the high-pressure tank and place it in an aging oven at 135°C for a high-temperature test for 1000 hours.

[0062] After the hydrolysis test, the specimens were taken out and the surface was wiped dry. After being placed in an environment of 23°C / 50%RH for 24 hours, the tensile performance test was performed in accordance with the international standard ISO 527-2-2019. The test conditions were: temperature 23°C, tensile rate 10mm / min. Tensile strength retention rate = tensile strength after hydrolysis test / tensile strength before hydrolysis test*100%. That is, the retention rate (1) / retention rate (2) in the following table correspond to the above hydrolysis test 1 / hydrolysis test 2 respectively.

[0063] Table 1: Contents (parts by weight) of components in the semi-aromatic polyamide compositions of Examples 1-7 and test results

[0064] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 PA6T6I-A 60 60 60 60 52 75 65 Glass Fiber A 30 Glass Fiber B 30 25 45 35 Glass Fiber C 30 Glass Fiber 30 Ethylene-octene copolymer 1 1 1 1 1 1 0 Initial tensile strength, MPa 246 235 232 223 233 254 242 Retention rate (1)% 87.0 84.7 84.0 82.9 84.5 87.0 85.1 Retention rate (2)% 58.1 53.6 53.4 52.9 53.6 59.1 55.0

[0065] It can be seen from Examples 1-4 that the smaller the diameter of the glass fiber, the higher the hydrolysis resistance.

[0066] Table 2: Contents (parts by weight) of components in the semi-aromatic polyamide compositions of Examples 8-15 and test results

[0067] Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Embodiment 15 PA6T6I-B 60 60 PA6T6I-C 60 PA6T6I-D 60 PA6T6I-E 60 PA6T6I-F 60 PA6T / 6I / 66-1 60 PA10T 60 Glass Fiber B 30 30 30 30 30 30 30 30 Ethylene-octene copolymer 1 1 1 1 1 1 1 EPDM 1 Initial tensile strength, MPa 206 230 221 226 218 220 202 220 Retention rate (1)% 88.3 90.2 91.3 89.3 85.3 86.8 91.6 88.9 Retention rate (2)% 56.2 61.2 62.0 60.1 54.1 56.8 68.8 57.2

[0068] It can be seen from Examples 1 / 8-10 that the semi-aromatic polyamide resin preferably has a terminal amine group concentration of 110-130 mol / t and a terminal carboxyl group concentration of 30-40 mol / t.

[0069] It can be seen from Examples 10-12 that the relative viscosity of the semi-aromatic polyamide is preferably 2.4-2.6.

[0070] It can be seen from Examples 13 / 14 that although PA10T has a higher retention rate, PA6T6I and PA6T / 6I / 66 are preferred based on the initial tensile strength value.

[0071] Table 3: Contents of components (parts by weight) and test results of the comparative semi-aromatic polyamide composition

[0072] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 PA6T / 6I-G 60 PA6T / 6I-H 60 PA6T / 6I-I 60 PA6T / 6I-J 60 PA66 60 PA66 / 6T 60 PA6T / 6I / 66-2 60 PA6T / 6I / 66-3 60 Glass Fiber B 30 30 30 30 30 30 30 30 Ethylene-octene copolymer 1 1 1 1 1 1 1 1 Initial tensile strength, MPa 238 242 237 223 208 226 218 220 Retention rate (1)% 79.8 70.7 72.2 68.4 55.8 62.3 65.3 69.7 Retention rate (2)% 43.3 37.8 41.7 36.2 27.9 33.6 35.1 37.4

[0073] It can be seen from Comparative Examples 1-4 / 7-8 that if the end group concentration of PA6T / 6I is not within the scope of the present invention, the hydrolysis resistance is poor.

[0074] It can be seen from Comparative Examples 5 / 6 that the technical solution of the present application is insufficient to improve the hydrolysis resistance of aliphatic polyamides such as PA66 and PA66 / 6T or other semi-aromatic polyamides.

Claims

1. A semi-aromatic polyamide composition, characterized in that: By weight, it includes the following components: 52-75 parts of semi-aromatic polyamide resin; Glass fiber 25-45 parts; Elastomer 0-3 parts; Wherein, the terminal amine concentration of the semi-aromatic polyamide resin is 110-130 mol / t, and the terminal carboxyl concentration is 30-40 mol / t; The average diameter of the glass fiber is 0.1-15 microns; The semi-aromatic polyamide resin is selected from at least one of PA6T / 6I, PA6T / 6I / 66 and PA10T; The relative viscosity of the semi-aromatic polyamide is 2.4-2.6, and the test method is to refer to GB / T 12006.1 polyamide viscosity determination method, and measure the relative viscosity of the polyamide with a concentration of 0.25 g / dL in 98% concentrated sulfuric acid at 25±0.01°C.

2. The semi-aromatic polyamide composition according to claim 1, characterized in that The semi-aromatic polyamide resin is selected from at least one of PA6T / 6I and PA6T / 6I / 66.

3. The semi-aromatic polyamide composition according to claim 1, characterized in that The diameter of the glass fiber is 0.1-8 microns.

4. The semi-aromatic polyamide composition according to claim 1, characterized in that The elastomer is selected from at least one of polyethylene elastomer, polypropylene elastomer, EPDM rubber and ethylene-octene copolymer.

5. The semi-aromatic polyamide composition according to claim 1, characterized in that By weight, the invention also includes 0-2 parts of auxiliary agents; the auxiliary agents are selected from at least one of antioxidants and lubricants.

6. The semi-aromatic polyamide composition according to any one of claims 1 to 5, characterized in that: The tensile strength retention rate of the semi-aromatic polyamide composition after aging in a cooling liquid at 135°C / 1000h is ≥50%.

7. The method for preparing the semi-aromatic polyamide composition according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder at a temperature range of 270-330 DEG C and a rotation speed range of 200-500 rpm to obtain a semi-aromatic polyamide composition.

8. Use of the semi-aromatic polyamide composition according to any one of claims 1 to 6, characterized in that: The hydrolysis-resistant parts are used for preparing hydrolysis-resistant parts, wherein the hydrolysis-resistant parts are selected from at least one of water pumps, water valves, thermostats, engine cooling water jackets, water pipe joints, and radiators.